Calcium signalling: methods and protocols - Raffaello, Anna; Vecellio Reane, Denis (Methods in molecular biology, 2019)
High-Throughput Screening using Photoluminescence Probe to Measure Intracellular Calcium Levels -- Exploiting Cameleon Probes to Investigate Organelles Ca2+ Handling -- Measuring Ca2+ Levels in Subcellular Compartments with Genetically-Encoded GFP-Based Indicators -- Methods to Measure Intracellular Ca2+ Concentration using Ca2+-Sensitive Dyes -- MCU Regulation in Lipid Bilayer and Electrophysiological Recording -- Electrophysiological Characterization of Calcium-Permeable Channels using Planar Lipid Bilayer -- Patch Clamp Analysis of the Mitochondrial Calcium Uniporter -- In Vivo Light Sheet Fluorescence Microscopy of Calcium Oscillations in Arabidopsis thaliana -- Ex Vivo Measurements of Ca2+ Transients in Intracellular Compartments of Skeletal Muscle Fibres by Means of Genetically Encoded Probes -- Imaging Intracellular Ca2+ in Cardiomyocytes with Genetically Encoded Fluorescent Probes -- In Vivo Monitoring of Ca2+ Uptake into Subcellular Compartments of Mouse Skeletal Muscle -- TRPML1/TFEB-Dependent Regulation of Lysosomal Exocytosis -- Ca2+-Dependent Regulation of TFEB and Lysosomal Function -- Employing Transgenic Parasite Strains to Study the Ca2+ Dynamics in the Human Malaria Parasite Plasmodium falciparum -- Calcium Imaging of Stored Operated Calcium (Ca2+) Entry (SOCE) in HEK293 Cells using Fura-2 -- Optogenetic Interneuron Stimulation and Calcium Imaging in Astrocytes -- Measuring Calcium and ROS by Genetically Encoded Protein Sensors and Fluorescent Dyes -- Assessing Calcium-Stimulated Mitochondrial Bioenergetics using the Seahorse XF96 Analyzer -- Determination of ATP, ADP, AMP Levels by Reversed-Phase High Performance Liquid Chromatography in Cultured Cells -- Purification of Functional F-ATP Synthase from Blue Native PAGE.